Hubungan Pengetahuan dan Status Gizi Dengan Kejadian Anemia pada Remaja Putri di Yayasan Pesantren Maruyung An-Nur Kabupaten Bandung - Hidayat, Monna Maharani Hidayat; Melanie, Ritha; Wisnusakti, Khrisna; Sabila, Amelia (JURNAL KESEHATAN KARTIKA, 2024)
Background: Anemia is a prevalent nutritional problem among adolescents, with a prevalence rate in Indonesia reaching 31.2% in 2019, higher than the 2018 rate of 30.4%. Knowledge and nutritional status are significant factors influencing the occurrence of anemia, particularly among adolescent girls. Objective: to identify the relationship between knowledge and nutritional status with the incidence of anemia among adolescent girls in Yayasan Pesantren Maruyung An-Nur. Method: This study employed an observational analytic design with a cross-sectional approach. The research sample comprised 83 adolescent girls selected using proportionate stratified random sampling. Data were collected using an Hb meter, a knowledge questionnaire, a microtoise, and a weighing scale. Data analysis was conducted using univariate and bivariate analysis with Fisher's Exact Test. Results: The study findings revealed that all adolescent girls with low knowledge experienced anemia (100%). Similarly, all adolescent girls with abnormal nutritional status also experienced anemia (100%). Bivariate analysis showed a significant relationship between knowledge and nutritional status with the incidence of anemia (p-value < 0.05). Conclusion: This study established a significant relationship between knowledge, nutritional status, and the incidence of anemia among adolescent girls in Yayasan Pesantren Maruyung An-Nur. Health education programs on anemia prevention and treatment are necessary to enhance knowledge and improve the nutritional status of adolescent girls in the school environment